PENGARUH KELEMBAGAAN LAHAN DAN TENAGA KERJA PADA USAHATANI TERHADAP KONSUMSI PANGAN DAN NON PANGAN PETANI DI KABUPATEN GUNUNG KIDUL - Suwarto Suwarto (Jurnal Dinamika Sosial Ekonomi, 2007)
This research aims to find out the effect of land and labor institutions on food and non food consumption in Gunung Kidul. The research was conducted by discriptive method. The result of this research shows that food and non-food consumption of the owrner-operator farmers are not different with the consumption of farmers in other land institutions. Food and non-food consumption of forestry tenant land are lower than the consumption of farmers in other land institutions. Food consumption of Lungguh-Kas Desa-Pengarem arem-milik Perseorangan (LKP) rented land is lower than the consumption of farmers in other land institutions. Food consumption based on labor institution of farming is not different. Non food consumption of farmers who employ royongan labor is higher than one of farmers in other labor institutions.Kerywords : land institutions, labor, consumption